2007
DOI: 10.1007/s00213-006-0659-x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of group II metabotropic glutamate receptors in stress-induced behavioural sensitization

Abstract: Shock-induced behavioural sensitization in rats is reduced by acute treatment with a group II metabotropic glutamate receptor agonist. This effect may depend on the increased expression of amygdala mGluR3, which could be hypothesized as an endogenous mechanism to counteract stress-induced neuronal sensitization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
1
0
0
Order By: Relevance
“…This is expected since mGluR3 reduces the excitatory effects of glutamate; hence the observed upregulation is due to the active excitatory mGluR5 receptor effect. This finding was corroborated by Stam et al [45], who reported that in their stressed animals, mGluR3 expression was elevated. Among the F 1 generation, it was observed that offspring born of any parent with history of PFS had increased expression of hippocampal mGluR3 mRNA with associated decrease in sucrose consumption when compared to rats born from male and female saline parents.…”
Section: Discussionsupporting
confidence: 78%
“…This is expected since mGluR3 reduces the excitatory effects of glutamate; hence the observed upregulation is due to the active excitatory mGluR5 receptor effect. This finding was corroborated by Stam et al [45], who reported that in their stressed animals, mGluR3 expression was elevated. Among the F 1 generation, it was observed that offspring born of any parent with history of PFS had increased expression of hippocampal mGluR3 mRNA with associated decrease in sucrose consumption when compared to rats born from male and female saline parents.…”
Section: Discussionsupporting
confidence: 78%